по алгебре 7 класс решебник ответы

Номер 992

Условие:

Решите уравнение:
а) (х + 1)(х + 2) - (х - 3)(х + 4) = 6;
б) (3x - 1)(2х + 7) - (х + 1)(6x - 5) = 7;
в) 24 - (Зу + 1)(4у - 5) = (11 - 6у)(2у - 7);
г) (6у + 2)(5 - y) = 47 - (2y - 3)(3y - 1).

 

Ответ:

а) (х + 1)(х + 2) - (х - 3)(х + 4) = 6 => x2 + 2x + x + 2 - (x2 + 4x - 3x - 12) = б => x2 - x2 + 3x - x = = 6 - 2 - 12 =>
=> 2x = -8 => x = -4;

б) (3x - 1)(2х + 7) - (х + 1)(6x - 5) = 7 => 6x2 + 21x - 2x - 7 - (6x2 - 5x + 6x - 5) = 7v6x2 - 6x2 + 19x - x = 7 + 7-5 =>
=> 18x = 9 => x = 0,5;

в) 24 - (Зу + 1)(4у - 5) = (11 - 6у)(2у - 7) => 24 - (12y2 - 15y + 4y - 5) = 22y - 77 - 12y2 + 42y =>
=> 12y2 - 12y2 + 11y - 64y = -77 - 24 - 5 => -53y = -106 => у = 2;

г) (6у + 2)(5 - y) = 47 - (2y - 3)(3y - 1) => 30у - 6y2 + 10 - 2y = 47 - (6y2 - 2y - 9y + 3) => -6y2 + 6y2 + 28y - 11y =
= 47 - 3 - 10 => 17y = 34 => у = 2.